Neutral Bremsstrahlung Emission in Xenon Unveiled - Henriques, C. A. O. (2022)
POPULAR SUMMARY When ionizing radiation interacts with xenon, copious amounts of ultraviolet light are emitted at particular wavelengths—an “electroluminescence” that is leveraged in dark matter searches and neutrino detectors. But researchers were not aware of the presence of another, fainter, light emission over a broader wavelength range, from the ultraviolet to the near infrared. Therefore, scientists explained the corresponding light pulses as being due to impurities in the gas. Here, we show that these pulses are instead signals of a new kind of light emitted in xenon, caused by the scattering of electrons onto neutral atoms. Using studies in a small laboratory system expressly conceived for this purpose, we identify this light—dubbed neutral bremsstrahlung—in the large detector of the NEXT experiment, an underground particle detector in Spain. Given the smallness of our detector, its xenon purity is very well controlled. In addition, we can precisely isolate the scintillation emission from a specific region of the detector and study this emission under very well controlled conditions, both when electroluminescence can and cannot occur. This allows us to observe and study scintillation emission other than electroluminescence. Simultaneously, we implement a robust theoretical model for the neutral bremsstrahlung, which describes the experimental data very well and allows us to unambiguously assign the observed scintillation mechanism to neutral bremsstrahlung. Now, scientists know that discovering dark matter and observing neutrinos requires more than just making the xenon pure inside of large detector systems. Researchers should also separate the light due to neutral bremsstrahlung to optimize the design of the detectors and to improve their sensitivity.